2005
DOI: 10.1002/yea.1298
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic study of introgression between Saccharomyces bayanus and S. cerevisiae

Abstract: The genomic constitution of different S. bayanus strains and natural interspecific Saccharomyces hybrids has been studied by genetic and molecular methods. Unlike S. bayanus var. uvarum, some S. bayanus var. bayanus strains (the type culture CBS 380, CBS 378, CBS 425, CBS 1548) harbour a number of S. cerevisiae subtelomeric sequences: Y , pEL50, SUC, RTM and MAL. The two varieties, having 86-100% nDNA-nDNA reassociation, are partly genetically isolated from one another but completely isolated from S. cerevisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
101
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 65 publications
7
101
0
2
Order By: Relevance
“…For the two strains with dual species introgression, this implies that progenitors of these strains either (1) successively hybridized with each of the other two species, or (2) hybridized with one of the other species, which already contained the other introgression. In all cases, it appears that the introgressed regions occur near or within subtelomeric regions (Naumova et al 2005(Naumova et al , 2011, and are found among the various strains in either homozygous (lacking equivalent S. cerevisiae sequences) or hemizygous states.…”
Section: Interspecific Hybridization and Introgressionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the two strains with dual species introgression, this implies that progenitors of these strains either (1) successively hybridized with each of the other two species, or (2) hybridized with one of the other species, which already contained the other introgression. In all cases, it appears that the introgressed regions occur near or within subtelomeric regions (Naumova et al 2005(Naumova et al , 2011, and are found among the various strains in either homozygous (lacking equivalent S. cerevisiae sequences) or hemizygous states.…”
Section: Interspecific Hybridization and Introgressionmentioning
confidence: 96%
“…Furthermore, introgression events, defined as a relatively small region of a different species' genome found within the genome of another species and mostly occurring within the closely related species of the Saccharomyces sensu stricto group, have also been detected (Naumova et al 2005;Liti et al 2006;Doniger et al 2008;Muller and McCusker 2009a,b;Naumova et al 2011). Horizontal gene transfer, in which genes are transferred from a distantly related organism (even transkingdom) through nonsexual mechanisms, has also been described among the Saccharomyces yeasts (Hall et al 2005;Novo et al 2009;Rolland et al 2009), although it may be relatively rare.…”
mentioning
confidence: 99%
“…This phenomenon was mentioned a few years ago for Saccharomyces, based on classical molecular genetic methods (32,148), and was recently extended using microsatellite typing (149). With complete genome sequences, introgression of delineated chromosomal fragments from one yeast species to another appears more frequent than initially anticipated.…”
Section: Traces Of Natural Introgressions In Yeast Genomesmentioning
confidence: 97%
“…The fact that this organism is an interspecific hybrid has been known for more than two decades (e.g., Nilsson-Tillgren et al 1981;Martini and Martini 1987; for reviews, see Kodama et al 2005;Smart 2007), and work since then has shown conclusively that different brewing yeast isolates can contain different combinations of the genomes (or partial genomes) of the following closely related Saccharomyces sensu stricto species: S. cerevisiae, Saccharomyces bayanus, Saccharomyces bayanus var. uvarum, and possibly a fourth, unknown "lagertype" species (Casaregola et al 2001;Naumova et al 2005;Rainieri et al 2006; for reviews, see Hornsey 2003;Kodama et al 2005). Pulsed-field gel/Southern blot analysis of several S. pastorianus strains has shown distinct differences in the distribution of transposable elements (Pederson 1985;Liti et al 2005), while array-CGH studies, using S. cerevisiae-only arrays, showed limited chromosomal changes among several strains (Bond et al 2004;Kodama et al 2005), also indicating complexity within this group.…”
mentioning
confidence: 99%